Development of an Ion-Pairing Reagent and HPLC-UV Method for the Detection and Quantification of Six Water-Soluble Vitamins in Animal Feed - Ho Jin Kim (International Journal of Analytical Chemistry)
A novel and simple method for detecting six water-soluble vitamins in animal feed using high performance liquid chromatography equipped with a photodiode array detector (HPLC/PDA) and ion-pairing reagent was developed. The chromatographic peaks of the six water-soluble vitamins were successfully identified by comparing their retention times and UV spectra with reference standards. The mobile phase was composed of buffers A (5 mM PICB-6 in 0.1% CH3COOH) and B (5 mM PICB-6 in 65% methanol). All peaks were detected using a wavelength of 270 nm. Method validation was performed in terms of linearity, sensitivity, selectivity, accuracy, and precision. The limits of detection (LODs) for the instrument employed in these experiments ranged from 25 to 197 μg/kg, and the limits of quantification (LOQs) ranged from 84 to 658 μg/kg. Average recoveries of the six water-soluble vitamins ranged from 82.3% to 98.9%. Method replication resulted in intraday and interday peak area variation of <5.6%. The developed method was specific and reliable and is therefore suitable for the routine analysis of water-soluble vitamins in animal feed.